Strengthening Web-Based Login Security Using Vigenère Cipher and AES ENCRYPT() Method in MySQL - Rhendy Diki Nugraha; Muhamad David Ali; Nadya Khairunnisa; Danang Nurcahyo; Ahmad Turmudi Zy (Journal of Technology and Informatics (JoTI), 2025)
As technology advances further, more crimes are being committed on social media. These days, people can connect to the internet using technological devices like PCs (Personal Computers) or portable electronic devices like smartphones or tablets. This study presents a dual-layer encryption system combining the Vigenère Cipher and MySQL’s AES_ENCRYPT() to enhance the security of web-based login systems. The system encrypts user credentials on the client side using the Vigenère Cipher and applies additional encryption on the server side with AES_ENCRYPT(). This approach ensures secure data transmission and storage, reducing risks of plaintext exposure and unauthorized access. Comparative testing demonstrated that the dual-layer encryption method significantly improves resistance to brute-force attacks and database breaches compared to conventional techniques like SHA-256. Encrypted credentials remain secure even in the event of a database compromise, as decryption requires the correct secret keys. The system’s design also highlights the importance of robust key management to maintain data confidentiality and integrity. While this method introduces minor performance overhead and requires careful implementation, its advantages in safeguarding sensitive user information outweigh these limitations. This dual-layer approach is particularly suited for applications demanding high-security standards, making it a viable solution for mitigating contemporary cyber threats effectively.